Benzimidazole‐based protein kinase inhibitors: Current perspectives in targeted cancer therapy. (19th August 2022) - Ali, Alaa M.; Tawfik, Samar S.; Mostafa, Amany S.; Massoud, Mohammed A. M.
Abstract: Targeted therapy has emerged to be the cornerstone of advanced cancer treatment, allowing for more selectivity and avoiding the common drug toxicity and resistance. Identification of potential targets having vital role in growth and survival of cancer cells got much easier with the aid of the recent advances in high throughput screening approaches. Various protein kinases came into focus as valuable targets in cancer therapy. Meanwhile, benzimidazole‐based scaffolds have gained significant attention as promising protein kinase inhibitors with high potency and varied selectivity. Great diversity of these scaffolds has inspired the medicinal chemists to inspect the effect of structural changes upon inhibitory activity on the molecular level through modeling studies. The present review gathers all the considerable attempts to develop benzimidazole‐based compounds; designed as protein kinase inhibitors with anticancer activity since 2015; that target aurora kinase, CDK, CK2, EGFR, FGFR, and VEGFR‐2; to allow further development and progression regarding benzimidazoles. Abstract : Targeted therapy has emerged to be the cornerstone of advanced cancer treatment, allowing for more selectivity and avoiding drug toxicity and resistance. Various protein kinases came into focus as valuable targets. Benzimidazole‐based scaffolds appeared as promising protein kinase inhibitors with high potency and varied selectivity.